Ethical design in manipulating interior spaces to arouse emotions / Aishath Rasiya - Rasiya, Aishath (2022)
Humans spend a significant time indoors. The innate interaction with the interior spaces makes it critical to identify the link between design features and the user's emotional states. The thesis aimed to create a framework for ethical design practice in promoting the social key of sustainability, with the objectives (i) to identify the ethical design issues and their impact on the end-user (ii) to identify architectural elements that could be manipulated to influence human emotions and (iii) to evaluate the influence of the renovated interior spaces on human emotions. Exploration of the ethical design required qualitative methods, i.e. interviews, observations and EEG qualitative readings, to find out the emotions evoked in the participants. This study confirms the inevitable notion that architecture significantly impacts human emotions. More importantly, the research has identified the elements or features in interior architecture that can be used to manipulate the negative emotions experienced by the user into positive emotions. By using content analysis of the data collected.